Study of the crystalline and optical properties of lithium tantalate thin films deposited by high power RF magnetron sputtering. (7th February 2017) - Pan, Dong; Wang, Jun; Sun, Binwei; Gou, Jun
Abstract: Lithium tantalate (LiTaO3 ) thin films were deposited by high power (250 W) RF magnetron sputtering on Pt/Ti/SiO2 /Si(100) substrates and were annealed from 600 °C–700 °C in an O2 or N2 environment. The crystallinity of those films were examined by x-ray diffraction and Raman spectra to study the effects of annealing temperature and annealing gas on the crystal properties of LiTaO3 thin films. LiTaO3 thin films annealing at 650 °C in O2 have a better crystalline quality in a (012) preferential orientation. However, LiTaO3 thin films annealed at 700 °C in O2 contain impurities with titanium oxide (Ta2 O5 ). This is attributable to the fact that the crystal structure is unstable above the Curie temperature and the tantalum reacts with oxygen in the annealing process. At the same time, the result of the Raman spectra suggests that LiTaO3 thin films annealed at 600 °C and 650 °C are closer to near-stoichiometric LiTaO3 and have less Li diffusivity and Li-deficient phases. Finally, optical constants of LiTaO3 films are also primarily probed by spectroscopic ellipsometry. For LiTaO3 thin films annealed at 650 °C in O2, the refractive index is 2.33, the extinction coefficient is 0.002 34 and the direct optical band gap energy is estimated to be minimal at 3.66 eV.